2017
DOI: 10.1093/cercor/bhx064
|View full text |Cite
|
Sign up to set email alerts
|

What's Behind a “+” Sign? Perceiving an Arithmetic Operator Recruits Brain Circuits for Spatial Orienting

Abstract: Do mathematical symbols evoke spatial representations? Although behavioral studies have long demonstrated interactions between space and the processing of Arabic digits, how to interpret these results remains controversial. Here, we tested whether activity in regions supporting spatial processing contributes to the processing of symbols conveying fundamental arithmetic concepts-such as operation signs-even in the absence of associated digits. Using functional magnetic resonance imaging, we show that merely per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 51 publications
11
32
0
Order By: Relevance
“…On the one hand, this suggests that increasing involvement of the MNL for solving arithmetic problems relies on the maturation of cognitive systems more than it relies on an increase in fluency per se. For example, neuroimaging studies have found that arithmetic problem solving relies on a network of brain regions supporting spatial attention 41,36 . However, these mechanisms are slow developing and additional structures might be required in children to learn how to navigate along the MNL 21 .…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, this suggests that increasing involvement of the MNL for solving arithmetic problems relies on the maturation of cognitive systems more than it relies on an increase in fluency per se. For example, neuroimaging studies have found that arithmetic problem solving relies on a network of brain regions supporting spatial attention 41,36 . However, these mechanisms are slow developing and additional structures might be required in children to learn how to navigate along the MNL 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this model, the neural structures recruited during addition and subtraction could resemble those observed during rightward or leftward eye movement, respectively ( Knops et al, 2009a ). The brain substrates implicated in spatial orienting even activate when an arithmetic operator (e.g., addition sign “+”) is shown ( Mathieu et al, 2017 ). In this account, because arithmetic only hijacks the horizontal-dimension spatial transformation system, the spatial compatibility effect does not extend to the vertical dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, there is a tendency to point more rightward after additions and more leftward after subtractions (spatial operational momentum-OM; [114,115]). And finally, addition and subtraction operations lead to enhanced perceptual sensitivity in the right and left side of space, respectively [116][117][118][119]. But also outside of SNAs, there are clear links between sensorymotor activities and arithmetic biases, such as making and breaking sets inducing addition and subtraction biases, respectively [120].…”
Section: A Practical Perspectivementioning
confidence: 99%